1992
DOI: 10.21273/hortsci.27.5.420
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Carbon Dioxide Treatment Enhances Firmness of Several Cultivars of Strawberry

Abstract: Various cultivars of strawberry (Fragaria ×ananassa Duch.) were stored for 42 h under an atmosphere of 15% CO2 to determine whether their firmness would be enhanced. Compared to initial samples and stored control samples, enhanced firmness was found in 21 of the 25 cultivars evaluated. The CO2 had no effect on color, as measured by Hunter `L', `a' and `b', or on soluble solids concentration (SSC) or pH. There were significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 3 publications
1
26
1
6
Order By: Relevance
“…Northeaster and Earliglow fruits became firmer during CO 2 treatment compared with fruit stored in air (Table 1). An increase in firmness in response to CO 2 storage is a common characteristic of strawberry fruit (Plocharski 1982; Smith 1992; Smith and Skog 1992; Larsen and Watkins 1995; Watkins and others 1999; Zhang and Watkins 2005). Fruit texture is related to adhesion between neighboring cells, cell fragility, and internal turgor pressure (Harker and others 1997), but the reasons for the CO 2 effect on firmness are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Northeaster and Earliglow fruits became firmer during CO 2 treatment compared with fruit stored in air (Table 1). An increase in firmness in response to CO 2 storage is a common characteristic of strawberry fruit (Plocharski 1982; Smith 1992; Smith and Skog 1992; Larsen and Watkins 1995; Watkins and others 1999; Zhang and Watkins 2005). Fruit texture is related to adhesion between neighboring cells, cell fragility, and internal turgor pressure (Harker and others 1997), but the reasons for the CO 2 effect on firmness are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable differences were detected both among treatments on eggplant pH (Table 2; Fig. 3) and for pH between modified atmosphere storage and air storage similarly to elsewhere reported data (Smith & Skog, 1992; Cordenunsi et al. , 2003).…”
Section: Phmentioning
confidence: 99%
“…In addition to the suppressing decay incidence and severity (Nunes et al, 2002), exposure of strawberry fruit to high pCO 2 has shown an increase fruit firmness, when provided either as a short-term flush of 100 kPa CO 2 (Goto et al, 1996;Hwang et al, 1999;Ueda and Bai, 1993) or in response to CO 2 accumulating in film-wrap packaging (Vicente et al, 2003). Elevated pCO 2 -mediated firmness increases in strawberry are significantly influenced by cultivar (Matsumoto et al, 2010;Pelayo et al, 2003;Smith and Skog, 1992;Watkins et al, 1999), pCO 2 (Goto et al, 1995;Harker et al, 2000), fruit maturity (Goto et al, 1995), and duration and temperature of exposure (Smith, 1992;Zhang and Watkins., 2005). CO 2 -induced firmness increases have also been reported for mango (Siriphanich, 1998).…”
Section: Introductionmentioning
confidence: 99%